DESCRIPTION OF CLINICAL CHARACTERISTICS OF DENTIN HYPERSENSITIVITY OF WORKERS IN THE CHEMICAL PRODUCTION INDUSTRY WITH ACID EXPOSURE (Vietnam Journal of Community Medicine, 2022)
Background: Dentin hypersensitivity is a common oral health problem, which is of great concern inthe world and in Vietnam.Objective: Determination of prevalence, clinical characteristics and related factors of dentinhypersensitivity of workers exposed to acids.Methods: Cross-sectional study.Results: This study collected information from 868 workers exposed to acids in Lam Thao SuperPhosphate and Chemical Joint Stock Company through questionnaires and examination andassessment of hurt related to dentin hypersensitivity. The research results show that the rate of dentinhypersensitivity in workers exposed to acid was 59.7%, of which molar group accounted for 60.0%.
Keywords: Dentin sensitivity, clinical characteristics, incidence, workers.